“ Effectiveness of Spencer Technique and Scapular Stabilization Exercises to improve pain and ROM in patients with Frozen Shoulder – A Comparative Study ” - Purbia, Neha; Pal, Renuka; Khan, Jafar; khan, Usman; Lohar, Deepak; Pinjara, Farukh Mohammad (Journal of Neonatal Surgery, 2025)
Background : Frozen shoulder also known as adhesive capsulitis is identified by initially painful and progresses to stiffness and decreased range of motion in the shoulder joint. The individuals gets usually affected in their mid-life which leads to difficulty in daily living activities. While various physiotherapy treatments are utilised for frozen shoulder, the comparative effect of Spencer and scapular stabilization exercises remains unknown. Aim : This study aims to evaluate and compare the outcomes of these two therapeutic approaches in managing frozen shoulder. Methods : A total of 40 subjects diagnosed with frozen shoulder were randomly assigned into two groups. Group A (n=20) received the Spencer technique, while Group B (n=20) underwent scapular stabilization exercises. Outcome measures included the Shoulder Pain and Disability index (SPADI), Numeric Pain and Rating scale (NPRS) and goniometric range of motion measurements. Pre and post post treatment values were statistically analyzed within and between groups, and evaluated before and after 6 weeks study period. Results : Both groups reveal changes in SPADI scores, NPRS scores and range of motion after six weeks. Their performance was calculated using independent t-test (between group comparison) and paired t-test (within group comparison). An independent t-test showed significant difference between the post-test results in two groups with P<0.05 and a paired t-test also showed larger mean improvement in Group A > Group B. However, Group A demonstrated greater improvements in flexion, extension, abduction, internal and external rotation range, along with greater reduction in pain and disability scores, compared to Group B. Conclusion : The Spencer technique was more effective than scapular stabilization exercises in enhancing clinical outcomes in frozen shoulder patients.